24-Hour Ambulatory Blood Pressure Monitoring Predicts Outcomes of Hypertensive Patients in Primary Care: A Cohort Study - Grezzana,Guilherme Brasil (2017)
Abstract Background: Arterial hypertension is an important risk factor for cardiovascular outcomes. However, in most Primary Health Care centers, blood pressure remains at inadequate control levels. Ambulatory Blood Pressure Monitoring (ABPM) is a useful tool in predicting cardiovascular morbidity and mortality. The implementation of 24-hour ABPM and evaluation of cardiovascular outcomes in Primary Health Care may be effective in improving strategies for monitoring hypertensive patients in this setting. Objective: To evaluate uncontrolled arterial hypertension detected by 24-hour ABPM as a predictor of cardiovascular outcomes in hypertensive patients from Primary Health Care in a low-resource environment. Methods: Cohort study based on primary health care centers. The study was carried out with 143 hypertensive patients, who underwent 24-hour ABPM at baseline. Therapeutic targets were based on the Eighth Joint National Committee, the Brazilian Hypertension Guideline, and the European Hypertension Guideline. Medical records of emergency care, hospital admissions, and death certificates were reviewed. Results: The sample consisted of 143 patients who met the inclusion criteria. After 4 years of follow-up, there were 17 deaths, 12 new cases of atrial fibrillation and 37 hospital admissions related to cardiovascular outcomes. During the follow-up period, the 24-hour ABPM showed a predictive result for new cases of atrial fibrillation (p = 0.015) and a combination of cardiovascular outcomes, mortality, and hospital admissions (p = 0.012). Conclusion: The 24-hour ABPM was an important predictor of cardiovascular outcomes in a hypertensive population that seeks assistance in Primary Health Care centers.